The Effect of Profitability and Leverage on Audit Delay in Consumer Goods Industry Companies Listed on the Indonesia Stock Exchange - Putri Maharani Fatiha silondae; Erwin Hadisantoso; Ika Maya Sari (Takaza Innovatix Labs Ltd., 2026)
This study aims to analyze the influence of profitability and leverage on audit delay in consumer goods industry companies listed on the Indonesia Stock Exchange. This study uses purposive sampling of 20 samples of financial statements of consumer goods industry companies listed on the Indonesia Stock Exchange. The method of data collection documentation uses. The analysis techniques used are descriptive analysis methods and multiple regression analysis with IBM SPSS Statistick software application version 25. The results of this study show that (1) Profitability has a significant effect on audit delays, this is because companies with a high level of profitability tend to want to convey their financial statements faster to the public as a form of strategy to convey positive information (good news). (2) Leverage has a significant effect on audit delays, this is because companies with large debt levels generally have an obligation to submit periodic financial statements to lenders or financial institutions, either as part of the terms in the credit agreement (loan covenant) as a form of accountability to maintain the reputation and trust of external parties. Therefore, the company tends to speed up the process of preparing financial statements so that the audit process can be completed early. (3) profitability and leverage have a significant effect on audit delays, this is because companies that have a high level of profitability and efficient leverage management tend to have better quality financial reporting, so that auditors can complete audits faster.